The new testament : - Harris, Stephen L. (McGrawHill, 2009)
The text surveys the historical and cultural background of the early Christian era and offers cogent discussions of each of the New Testament’s twenty-seven books, from the Gospel biographies of Jesus to the mystic symbols of Revelation. In addition to presenting the Jewish and Greco-Roman context in which the canonical authors wrote, the text incorporates important scholarship that helps illuminate each document’s principal themes and religious significance.